The united innovation process: integrating science, design, and entrepreneurship as sub-processes. (27th October 2015) - Luo, Jianxi
Abstract : 'Innovation' has become a buzzword in academic papers, news articles, and book titles, but it is variously defined and is often referred to as 'invention' or 'design'. A consensus of understanding the interrelationships of the concepts and activities pertaining to innovation is needed to guide collective action for innovation. This paper proposes a united view of the innovation process, which advocates uniting the complementary (1) science, (2) design, and (3) entrepreneurship sub-processes of innovation. The shared creative, uncertain, and costly nature of these three processes also implies an opportunity to leverage design science to understand and guide the science and entrepreneurship processes. This paper describes the benefits, major challenges, and actionable strategies for uniting science, design, and entrepreneurship as sub-processes of innovation, with a few detailed real life examples. The variety of the cases and examples shows that science, design, and entrepreneurship sub-processes can be effectively united to different extents, within and across organizations and innovation ecosystems.